Simulation and Optimization of Fatigue Life of Carbon-Epoxy Composite Sub Frame - Roohollah Talebitoot; Seyedmahdi Seyedraoufi (Mechanics of Advanced Composite Structures)
Recently, automotive companies are interested in the usage of composite materials, because of their mechanical properties such as high strength-to-weight ratio, high stiffness, and flexibility in layout configurations. In the present work, fatigue failure was determined based on Lessard and Shokrieh progressive model in composite sub-frame subjected to fatigue loading in its service life, and a genetic algorithm was used to find the optimum stacking sequence to achieve maximum fatigue life. According to the results, [±454/012]s laminate was determined as the optimum orientation. Since the simulation results have shown usage of 90◦ layers as consecutive plies end up a progression of matrix damage and increase of stress while using ±45◦ layers as outer layers lead to increase the stiffness, toughness, and impact resistance of laminate and postpone the failure in laminate. It can be seen that the elements failed in matrix and delamination modes around 40% and 50% of total life, respectively. Moreover, before catastrophic failure, 7%, 8.55%, and 13% degradation happened in longitudinal, transverse, and shear stiffness respectively. Like wisely, 20%, 23%, and 46% degradation occurred in longitudinal, transverse, and shear strength discretely.